Neurolaw and Ageing: A Bioethical Approach to Cognitive Enhancement (Revista Iberoamericana de Bioética, 2022)
Advances in neuroscience are leading to decisive changes in people’s lives, and in ethics and legal fields. In this framework, neurotechnological development and applications are called upon to improve human beings’ quality of life and welfare, especially the elderly, to the extent that measures like neuroenhancement are shaped as effective tools in the fight against the impairment of cognitive functions. However, to use such resources can create risks for humankind’s privacy and mental integrity, which makes it necessary to recognise neurorights, in order to avoid meddling without informed consent.
Keywords: neurolaw; healthy ageing; neurorights; neuroenhancement; bioethics